“It Don’t Mean a Thing if It Ain’t Got that Swing”– an Alternative Concept for Understanding the Evolution of Dance and Music in Human Beings - Richter, Joachim; Ostovar, Roya (Frontiers in Human Neuroscience, 2016)
The functions of dance and music in human evolution are a mystery. Current research on the evolution of music has mainly focused on its melodic attribute which would have evolved alongside proto-language. Instead, we propose an alternative conceptual framework which focuses on the co-evolution of rhythm and dance (R&D) as intertwined aspects of a multimodal phenomenon characterized by the unity of action and perception. Reviewing the current literature from this viewpoint we propose the hypothesis that R&D have co-evolved long before other musical attributes and (proto)-language. Our view is supported by increasing experimental evidence particularly in infants and children: beat is perceived and anticipated already by newborns and rhythm perception depends on body movement. Infants and toddlers spontaneously move to a rhythm irrespective of their cultural background. If this behavior is universal, R&D must have an essential function in human evolution. Conceivable evolutionary functions of R&D include sexual attraction, transmission of mating signals, synchronization of many individuals, social bonding, appeasement of hostile individuals, pre- and extra-verbal communication, improvement of body coordination, as well as pain killing, anti-depressive, and anti-boredom functions. The impulse to dance may have been prepared by the susceptibility of infants to be soothed by rocking. Dance enables embodied individual and collective memorizing; in many cultures R&D are used for entering trance, a base for shamanism and early religions. Rhythm is necessary to codify human speech and dance encompasses gesture. In future studies attention should be paid to which attribute of music is focused and that the close mutual relation between R&D is taken into account. The possible evolutionary functions of dance deserve more attention.